2016
DOI: 10.5578/ttj.17.1.002
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia: A Risk Factor of Mortality for Patients with Sepsis in the Intensive Care Unit

Abstract: OBJECTIVES:The objective of this study was to evaluate the intensive care unit (ICU) and long-term mortality in sepsis patients with/ without thrombocytopenia on the fifth day of ICU admission. MATERIALS AND METHODS:The retrospective observational cohort study was performed in a teaching hospital, and patients with sepsis who stayed more than 4 days in the ICU between January 2012 and December 2012 were included. Patients were divided into two groups according to thier platelet count at fifth day of ICU stay: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…The search strategy identified 2820 studies, and the data were from 7 studies comprising 4243 patients (Table 2) [18][19][20][21][22][23][24]. The characteristics of the included studies are shown in Table 2.…”
Section: Results 31 Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy identified 2820 studies, and the data were from 7 studies comprising 4243 patients (Table 2) [18][19][20][21][22][23][24]. The characteristics of the included studies are shown in Table 2.…”
Section: Results 31 Study Characteristicsmentioning
confidence: 99%
“…Among these studies, 2 studies were conducted in France, 1 study was conducted in Isreal, 1 study was conducted in USA, 1 study was conducted in Turkey, 1 study was conducted in Greece, 1 study was conducted in The Netherlands. Of these studies, two of the studies were multi-center studies [20,23], and five were single-center studies [18,19,21,22,24]. Table 2 The basic characteristics of studies included in meta-analysis The short-term mortality of thrombocytopenia group was higher than that of the no thrombocytopenia group (odds ratio [OR] = 2.01;95% CI, 1.73-2.33; P < 0.00001;Chi 2 = 26.86; I 2 = 78%) (Fig.…”
Section: Results 31 Study Characteristicsmentioning
confidence: 99%
“…Several other studies evaluated septic shock in cancer patients, but they included patients with sepsis and septic shock, with the proportion of septic shock patients ranging between 25 and 60% of the study population [ 4 , 7 , 13 19 , 21 , 23 , 24 ]. Lemiale et al [ 23 ] recently published the characteristics and outcomes of a large cohort of cancer patients treated with sepsis and septic shock at 7 European ICUs over two decades (1994–2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the importance of low platelet in prognostication is well described in multiple studies in critically ill patients. Various patterns such as low nadir platelet count, or rapid decline in platelet count have proven significance based on several studies [ 42 , 43 ]. The evidence so far has confirmed a low platelet count as an important prognostic indicator of severity and mortality in COVID-19 patients [ 44 ].…”
Section: Platelet Abnormalities and Covid-19mentioning
confidence: 99%